Pengaruh Brand Image Dan Harga Produk Wardah Terhadap Keputusan Pembelian Secara Online Pada Mahasiswa Program Studi Pendidikan Ekonomi Di Universitas HKBP Nommensen Pematang Siantar - Hotma Jelita Lucyana A. Napitu; Binsar Tison Gultom; Anton Luvi Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to gain knowledge regarding the influence of Brand Image and Price on Online Purchasing Decisions among Female Students of the Economic Education Study Program at HKBP Nommensen University Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 303 people, and the sample used was 170 people. The sample collection technique used was a purposive sampling technique. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of this research state that: 1. There is a positive influence of brand image on purchasing decisions. This result can be seen in the t test where the calculated value of brand image (4.424) > t table (1.6540) which means this variable is significant. 2. There is a positive and significant influence of price on purchasing decisions. This result can be seen from the t test where the t value of price (5.102) > compared to t table (1.6540) which means that this variable has an effect but is not significant. 3. Brand Image and Price together influence purchasing decisions which can be seen in the test F where the Fcount value (62.578) is greater than the Ftable value (2.66). 4. The R Square coefficient of determination test is 0.428. Which means that 42.8% of the brand image and price variables influence the purchasing decision variables of economic education study program students at HKBP Nommensen Pematang Siantar University. Meanwhile, 57.2% is the influence of other variables not examined in this research.